Effect of herbicide stress on synchronization of carbon and nitrogen metabolism in lentil (Lens culinaris Medik.) - Shivani (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.